2014
DOI: 10.1080/14786435.2014.959579
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural properties of nanocrystalline PbS thin film grown by CBD on Si(1 0 0) substrate

Abstract: PbS nanocrystalline thin film was prepared by chemical bath deposition on Si (1 0 0) substrate at bath temperatures of 25, 45 and 65°C. Triethanolamine was added to the aqueous solution, which decreased the grain size and increased the luminescence of the nanocrystalline PbS thin film. PbS nanocrystals were identified using XRD, TEM and AFM. The crystalline size of the PbS film deposited at different bath temperatures was estimated by XRD and TEM to be 7-12 nm. The growth mechanism of the PbS crystallites were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…4(a)) corresponds to higher energy band transi-tions [29,30]. Similar luminescence was measured on PbS nano-cubes and thin films in other works by Cao et al [31] and Tohidi et al [32]. The inset of Fig.…”
Section: Resultssupporting
confidence: 82%
“…4(a)) corresponds to higher energy band transi-tions [29,30]. Similar luminescence was measured on PbS nano-cubes and thin films in other works by Cao et al [31] and Tohidi et al [32]. The inset of Fig.…”
Section: Resultssupporting
confidence: 82%
“…The strong peak observed at 580 nm corresponds to green emission. Recently, Cao et al and Tohidi et al observed the emission peaks at around 440 nm using the excited wavelength 330 nm for PbS thin films. They addressed that the observed PL emission at approximately 440 nm signifies the electrons transition from the conduction band edge to holes, present in interstitial Pb 2+ sites.…”
Section: Resultsmentioning
confidence: 99%
“…As the crystalline size decreases, the amount of ions quickly increases on the surface of the thin film. Moreover, the rate of carrier recombination increases as the size decrease because of the increase in overlap between the electron and hole wave functions …”
Section: Resultsmentioning
confidence: 99%